Ambulatory Rehabilitation of Patients with Parkinson’s Disease - Lebed, O.; Perkova, H. (Journal of Education, Health and Sport, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that causes motor and non-motor impairment, leading to reduced independence and quality of life. Pharmacological therapy alleviates symptoms but does not prevent functional decline, emphasizing the importance of multidisciplinary rehabilitation. Ambulatory programs, which combine physiotherapy, occupational therapy, and psychoeducation, offer an accessible and sustainable model of long-term management. Objective: To evaluate the effectiveness of a structured ambulatory rehabilitation program on motor performance, daily functioning, and quality of life in patients with idiopathic Parkinson’s disease. Materials and Methods: Sixty-eight patients with PD (Hoehn and Yahr stages II–III) participated in a twelve-week multidisciplinary outpatient program comprising physiotherapy, occupational therapy, speech and swallowing exercises, and psychoeducational counseling, three times weekly. Clinical outcomes were measured using the Unified Parkinson’s Disease Rating Scale (UPDRS II–III), Timed Up and Go (TUG), Six-Minute Walk Test (6MWT), Parkinson’s Disease Questionnaire-39 (PDQ-39), and Beck Depression Inventory-II (BDI-II). Data were analyzed with paired t-tests and multivariate regression (Statistica 14.1). Results: UPDRS total score improved from 52.6 ± 8.7 to 41.2 ± 7.9 (p < 0.001). TUG time decreased from 15.8 to 12.4 s, and 6MWT distance increased from 312 to 368 m (p < 0.05). PDQ-39 and BDI-II scores also showed significant improvement. Regression analysis (R²=0.524) identified shorter disease duration (β = −0.46, p = 0.002) and higher exercise adherence (β = 0.49, p < 0.001) as independent predictors of functional gain. Conclusion: Ambulatory multidisciplinary rehabilitation significantly improved motor function, endurance, and psychosocial well-being in moderate PD. Early initiation and consistent participation were key determinants of therapeutic success.